Everyday Inclusions: Rethinking Ethnocracy, Kafala, and Belonging in the Arabian Peninsula. (December 2015) - Vora, Neha; Koch, Natalie
Abstract: Scholarship on Gulf Cooperative Council (GCC) states, which have the highest proportions of migrants in the world, usually explores how they are unique in their patterns of non‐citizen exclusion. However, state discourses, geographies, and the heterogeneity of migration to the Gulf share similar traits with contemporary nations and states. Non‐citizens are, as they are everywhere, active participants in Gulf state‐ and nation‐building projects. Aiming to advance scholarship on belonging in the GCC states, in this paper, we propose a shift in focus from exclusion to inclusion in the way research questions are asked about Gulf societies and the people who reside in them. Doing so, we suggest, requires unpacking two hegemonic concepts in the regional studies scholarship: 'ethnocracy' and kafala . In their current usage, both terms have become 'black boxed', or reified, such that scholars have largely come to accept and reproduce the exceptionalism of the Gulf and refrain from asking a number of critical questions about the region, which might highlight the GCC states' fundamental normalcy . Through a reflexive approach that draws from our own previous and current research in the United Arab Emirates and Qatar, we suggest ways that we might move beyond the rigidity of exclusion‐centred narratives about the Gulf and instead consider the various ways that Gulf nationalisms themselves hail the non‐citizen presence, and how non‐citizens participate in discourses and practices of nationalism as well as statecraft in ways that cannot be reduced to nationality, class, race, or religion.